1997
DOI: 10.1002/(sici)1096-9063(199702)49:2<169::aid-ps520>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of s-Triazine Herbicides and Related Degradation Products in Liquid Cultures by the White Rot Fungus Phanerochaete chrysosporium

Abstract: : The ability of the white rot basidiomycete Phanerochaete chrysosporium to transform s-triazine herbicides has been investigated in laboratory experiments. The chlorinated metabolites formed during atrazine Ndealkylations were not further transformed by the fungus, whereas hydroxyatrazine was converted to an unknown product. P. chrysosporium was also able to carry out the N-dealkylation of the herbicides simazine, propazine and terbuthylazine. Herbicide metabolism was not supported by puriÐed peroxidases. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 0 publications
3
28
0
3
Order By: Relevance
“…In general, soil fungi remove the ethyl group of atrazine before the removal of the isopropyl group [36,37]. ), regarding not only the optimal percentage of degradation (4,11,12) but also the results that showed minimum medium composition (1) and unidentified metabolites (13,16). Another interesting result was obtained from assay 4, which promoted 60% atrazine degradation after 20 days with the formation of DIHA, DEDIA, DIA, HA and DEA.…”
Section: Optimization Of Atrazine Degradation Through Factorial Designsupporting
confidence: 86%
See 2 more Smart Citations
“…In general, soil fungi remove the ethyl group of atrazine before the removal of the isopropyl group [36,37]. ), regarding not only the optimal percentage of degradation (4,11,12) but also the results that showed minimum medium composition (1) and unidentified metabolites (13,16). Another interesting result was obtained from assay 4, which promoted 60% atrazine degradation after 20 days with the formation of DIHA, DEDIA, DIA, HA and DEA.…”
Section: Optimization Of Atrazine Degradation Through Factorial Designsupporting
confidence: 86%
“…The degradation and mineralization of atrazine can occur through physical-chemical processes or by microorganism action. Previous studies reported in the literature have identified more than 15 metabolites resulting from atrazine degradation [9][10][11][12][13]. The main atrazine degradation products are hydroxylated and chlorinated compounds, including desethylatrazine (2-chloro-4-amino-6-isopropylamine-s-triazine, DEA), desisopropylatrazine (2-chloro-4-ethylamine-6-aminos-triazine, DIA), desethyldesisopropylatrazine (2-chloro-4,6-aminos-triazine, DEDIA), desethylhydroxyatrazine (2-hydroxy-4-amino-6-isopropylamine-s-triazine, DEHA), desisopropylhydroxyatrazine (2-hydroxy-4-ethylamine-6-amino-s-triazine, DIHA) and hydroxyatrazine (2-hydroxy-4-ethylamine-6-isopropylamine-s-triazine, HA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to da Silva Coelho-Moreira et al [75], enzymatic crude extracts supplied with combinations of veratryl alcohol H 2 O 2 and Mn 2+ did not degrade the herbicide, it is possible that DCPMU and DCPU can be further transformed by MnP. P. chrysosporium is also able to transform atrazine, its transformation product and other striazine herbicides [70]. The first and main step in the chlorinated-s-triazine degradation pathway by the fungus was mono-N-dealkylation.…”
Section: +mentioning
confidence: 91%
“…MCPA and bentazon were degraded by P. chrysosporium at 65% and 75%, respectively, in 20 days [73]. P. chysosporium degraded isoproturon belonging to phenylurea groups [73,76], atrazine [70], and also diuron [82]. However, according to [57], no atrazine degradation was observed by this fungus in liquid cultures.…”
Section: +mentioning
confidence: 97%